Assessing the financial distress risk of companies operating under conditions of a negative cash conversion cycle - Aleksandra Szpulak (e-Finanse: Financial Internet Quarterly, 2016)
The purpose of the paper is to point out the accounting-based variables and relationships between them which enable us to measure financial liquidity in a way appropriate for assessing the financial distress risk of companies operating under conditions of a negative Cash Conversion Cycle (CCC). Contrary to the mainstream literature on bankruptcy predictions, mainly based on data modelling nested in statistics, in this article the approach is taken on modelling the bankruptcy process relevant for companies operating under conditions of negative CCC. The applied research methodology adopts Monte Carlo simulations based on a spreadsheet financial model of company operations built to simulate operating cash inflows and outflows generated by companies operating under negative CCC (following a methodology of a spreadsheet approach to financial modeling and risk analysis given by Charnes (2007)). To define financial liquidity measures the concept of Net Liquid Balance (Shulman & Cox, 1985) and cash investment in Operating Working Capital (Szpulak, 2014) is applied. The results enable us to overcome the insufficiency of existing financial liquidity indicators for assessing the financial distress of companies operating under conditions of negative CCC. The additions to theory and practice consist of theoretical underpinnings of a financial distress mechanism possible for companies operating under conditions of negative CCC and definition of financial liquidity measures relevant for these companies.
Keywords: G33; 330; financial liquidity; Cash Conversion Cycle; Operating Working Capital; Net Liquid Balance; Financial Distress; spreadsheet approach to financial modeling; Monte Carlo simulation